Republic of San Marino : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of San Marino. (IMF Staff Country Reports; Country Report, 2019)
This Article IV Consultation highlights that deep-rooted weaknesses in the banking system have undermined economic activity and are now threatening financial stability and fiscal sustainability. Significant deposit outflows have left the banking system with low liquidity, while persistent losses and high non-performing loans (NPLs) resulted in sizable recapitalization needs, particularly in the state-owned bank. Growth is projected to remain subdued in the coming years, reflecting continued banking sector deleveraging and a less favorable external environment, most notably in Italy. Slow progress in repairing the banking sector, and full and upfront recognition of the state's financial commitments to the banking system are the key risks. Urgent actions are needed to restore banking sector viability and credit supply, safeguard public finances, and promote sustained economic growth. It is recommended to strengthen labor supply by better targeting social benefits and further relaxing the hiring process of non-residents.